Preservation of Lymphopoietic Potential and Virus Suppressive Capacity by CD8+ T Cells in HIV-2-Infected Controllers. - Angin, M; Wong, G; Papagno, L; Versmisse, P; David, A; Bayard, C; Muylder, B; Besseghir, A; Thiébaut, R; Boufassa, F; Pancino, G; Sauce, D; et al. (American Association of Immunologists, 2016)
Compared to Human immunodeficiency virus 1 (HIV-1), HIV-2 infection is characterized by a larger proportion of slow or non-progressors. A better understanding of HIV-2 pathogenesis should open new therapeutic avenues to establish control of HIV-1 replication in infected patients. Here, we studied the production of CD8+ T cells and their capacity for viral control in HIV-2 controllers from the French ANRS CO5 HIV-2 cohort. HIV-2 controllers display a robust capacity to support long-term renewal of the CD8+ T-cell compartment by preserving immune resources, including hematopoietic progenitors and thymic activity, which could contribute to the long-term maintenance of the CD8+ T-cell response and the avoidance of premature immune aging. Our data support the presence of HIV-2 Gag-specific CD8+ T-cells that display an early memory differentiation phenotype and robust effector potential in HIV-2 controllers. Accordingly, we show for the first time that HIV-2 controllers possess CD8+ T-cells that show an unusually strong capacity to suppress HIV-2 infection in autologous CD4+ T- cells ex vivo, an ability that likely depends on the preservation of host immune resources. This effective and durable antiviral response probably participates in a virtuous circle, during which controlled viral replication permits the preservation of potent immune functions, thus preventing HIV-2 disease progression.